Otitis Externa: Investigation and Evidence-Based Treatment - Wiegand, Susanne (Dtsch Arztebl Int, 2019)
BACKGROUND: Otitis externa has a lifetime prevalence of 10% and can arise in acute, chronic, and necrotizing forms. METHODS: This review is based on publications retrieved by a selective search of the pertinent literature. RESULTS: The treatment of acute otitis media consists of analgesia, cleansing of the external auditory canal, and the application of antiseptic and antimicrobial agents. Local antibiotic and corticosteroid preparations have been found useful, but there have been no large-scale randomized controlled trials of their use. Topical antimicrobial treatments lead to a higher cure rate than placebo, and corticosteroid preparations lessen swelling, erythema, and secretions. Oral antibiotics are indicated if the infection has spread beyond the ear canal or in patients with poorly controlled diabetes mellitus or immunosuppression. Chronic otitis externa is often due to an underlying skin disease. Malignant otitis externa, a destructive infection of the external auditory canal in which there is also osteomyelitis of the petrous bone, arises mainly in elderly diabetic or immunosuppressed patients and can be life-threatening. CONCLUSION: With correct assessment of the different types of otitis externa, rapidly effective targeted treatment can be initiated, so that complications will be avoided and fewer cases will progress to chronic disease.